Impact of Mental Fatigue on Self-paced Exercise - Brownsberger, J.; Edwards, A.; Crowther, R.; Cottrell, D. (International Journal of Sports Medicine, 2013)
The purpose of this study was to examine whether mental fatigue influences the perceived effort required to complete fairly light and hard effort self-paced exercise challenges. 12 participants completed 2 trials in a randomised cross-over design. Each participant was required to complete a time-matched pre-exercise task: 1) a continuous cognitive activity test (EXP condition; n=12), or 2) a time-matched passive neutral observation task (CON condition; n=12). Following the pre-exercise task, participants performed 2 consecutive bouts of self-paced cycling exercise again in randomized order at fairly light (RPE 11) and hard (RPE 15) effort. Physiological, psychological and EEG indices were measured throughout both conditions. EXP participants reported significantly greater sensations of fatigue (p<0.01) and demonstrated greater EEG beta-band activation compared with CON (p<0.01) prior to exercise. Power outputs from the exercise bouts were significantly reduced for EXP in both self-paced: RPE 11 (83±7 vs. 99±7 W;  p=0.005) and RPE 15 (132±9 vs. 143±8 W; p=0.028) trials. This study demonstrates that individuals with higher self-reported sensations of fatigue and elevations of EEG beta activity in the prefrontal cortex of the brain prior to exercise produce less work during self-paced exercise trials than in a control condition, probably due to an altered perception of effort.
Keywords: mental fatigue; effort perception; brain regulation; pacing; EEG